(untitled) (Journal of the College of Basic Education, 2022)
Evaluation is the means through which the curriculum achieves the goals set for it, detects the positive and negative aspects in it, and notes the aspects in which the curriculum is effective and the other aspects that require modification, and since the Department of Architectural Design and Decoration at the Institute of Applied Arts is one of the institutions that aims to prepare A middle staff specialized in designing and decorating buildings. The purpose is to prepare a curriculum in the light of scientific development. Based on the above, the researcher has conducted his current research, which aims to evaluate the curriculum of planning and colors in the Department of Architectural Design and Decoration.